Comparison of the Handling of Homeless and Beggars in Medan and Jakarta Cities - Thamrin, Husni; Pribadi, Muhammad Akbar; Ridho, Hatta; Hanim, Farida (Journal of Ecohumanism, 2024)
Homelessness and begging are social problems that affect community welfare and demonstrate inequalities in access to basic resources, which require a holistic approach to address. Although Medan City and Jakarta City have implemented strict policies and dealt with homeless people, there are still many homeless people who return after being rehabilitated. Therefore, this research seeks to explain the comparison of the handling of vagrants and beggars by the governments of Medan City and Jakarta City. This research uses a qualitative method with a case study approach to analyze the differences in policies for handling vagrants and beggars in Medan City, North Sumatra Province, and Jakarta City, DKI Jakarta Province. The data collection techniques used were observation, interviews, focus group discussions, and secondary data derived from documents, reports, and publications. This research concludes that handling vagrants and beggars in Medan City and Jakarta requires a comprehensive and collaborative approach between the government, related institutions, and the community. In Jakarta, Governor Regulation No. 169 Year 2014 is the basis for the handling, while in Medan, two local regulations, namely Local Regulation No. 4 Year 2008 and Local Regulation No. 6 Year 2003, are the foundation. The main challenge in Jakarta is the need for massive program evaluation, while in Medan, the challenges include the lack of facilities and infrastructure, limited human resources, and lack of communication between related institutions. The Jakarta Government established Social Services, Supervision, and Control to deal with the problem. At the same time, in Medan, there is an Operation to Control Homeless Beggars and Street Children, which requires a holistic approach to handling. Differences also exist in the rehabilitation program, which must address the factors that influence begging and provide medical, psychological, and social support.